The Pedagogical Axiology of Mykhailo Halushchynsky (1878–1931) - Czepil, Marija (Biografistyka Pedagogiczna, 2022)
The article reveals the values of education in the creative legacy of Ukrainian educator, scholar and public figure Mykhailo Halushchynsky (1878–1931). The problems of the purpose, content, means and institutions of education, the role of education in the formation of the national consciousness of children and youth are emphased. In this publication, an attempt is made to reveal Halushchynsky’s contribution to the development of adult education, to the study of educational activities in Ukraine and foreign countries, and to the solution of the “I or society” dilemma. His life and activities are an example of service to his native people, tireless struggle for the realization of the national idea. Pedagogical heritage is a valuable source of knowledge for teachers and parents, which covers a wide range of issues related to the education of Ukrainian youth and extracurricular education.